Pengendalian Kualitas Berdasarkan Peta Kendali P Di Krakatau steel (Persero) - Sumadiono . (The Asia Pacific Journal Of Management Studies, 2014)
Quality is a key factor that brings the success of a production, growth and improvement of the competitive position of the company. To continue to maintain consistency and the existence of a quality product, we conducted qualities. Our control wire rod (wire rod) is one of the products produced in the PT. Krakatau Steel (Persero) Tbk, from observation data available, the number of types of defects or defective product in August 2014 there are 6 known types, namely: Coil cut in the middle, rumpled, over-fill, under fill, laps, creep speed and other defect. Number biggest defect is the defect tangle trait: 72 214 tons. Analysis of observations using P control chart with UCL LCL 2:58 15.05 and, known defect tangled in the wire rod products there that exceeds the upper control limit which occurred on August 29, 2014, with many disability 38.319 tons. It can be concluded in this case the production process must be improved and enhanced so that the occurrence of defects in the wire rod products can be prevented/ avoided.